Effect of stone crusher dust pollution on Wheat (Triticum sp.) crop - Chaurasia, Sadhana; Karan, Raj (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
This study was aimed to know the effect of stone crushers dust pollutant Viz. PM10 and PM2.5 on morphological as well as yield characteristics of wheat (Triticum sp.) plant growing at different distance from the stone crusher industry at Kabrai, Mahoba, U.P. India. The wheat plant near the industry showed deterioration in morphological characteristics. The study indicated that parameters reduction in wheat correlated directly with particulate pollutant which leads to lower yield at more polluted site. It was observed that wheat plant near the stone crushers industry having morphological reduction in growth and yield and as the distance from stone crushers industry increases growth and yield also increase. Over all study shows that control plants were healthier in term of morphological and yield parameter. It was found that wheat plant growing near the stone crusher industry was adversely affected. The areas around the stone crusher are constantly polluted by dust that spread in the atmosphere, thus causing damages to the environment and the resident’s lives nearby. So it is clear that the stone crushers dust pollution is an operative ecological factor causing deterioration in the quality of our environment.